'Remaking Greater Britain': Cecil Rhodes and imperial politics, 1880-1902 - Hunt, DM (2021)
This study asks how and why and to what effect Cecil Rhodes operated in British imperial politics from around his formal entry into politics in 1880 to his death in 1902. It shows that Rhodes used a network of ideologically coherent lobbyists operating mainly in London, but also from South Africa, to influence British imperial policy in Westminster and Whitehall; it examines the techniques that he and this group deployed, including in relation to the press. A detailed analysis of Rhodes’ role in British imperial politics has not yet been undertaken, a gap in the historiography which this study rectifies. Rhodes is positioned as a case study for how settler states and their leaders related to Britain as the centre of imperial power and decision making and shows that Rhodes envisaged a closer constitutional arrangement for the British Empire, based on the principles of ‘Greater Britain’. This brings new emphasis to the political exchange between London and the settler states which has been explored less by the British world school in recent decades than other areas such as culture, identity and migration. ‘Greater Britain’ is used as an interpretive framework for the analysis of the period and its practical counterpart ‘imperial federalism’ is placed in the mainstream of British political debate. I suggest that imperial federalism was closely related to the issue of British unionism, and therefore Irish nationalism, highlighting the presence of unionists, whose careers had been affected by Home Rule, in and around the movement for imperial federation – which shows the importance of Ireland to Rhodes’ career and to British imperial politics more widely during the period.